Principles Of Parliamentarism In The Context Of Western Armenian Constitutional Culture - Sarvazyan, Lilit (ՀՀ ԳԱԱ)
The Western Armenian constitutional movement, as a unique attempt in the East to modernize the national administrative system based on parliamentary principles, has been interpreted by many Armenian and foreign thinkers. In the context of the historical and political realities of the 19th-century Ottoman Empire, foreign authors tried to understand the level of the Armenian nation’s constitutional and legal consciousness, its capacity for self-government, the degree of its assimilation of European culture, and the essence of its system of governance. Within national circles, Western Armenian constitutionalism has been studied from various perspectives and with certain considerations, especially with the aim of predicting the nation’s political prospects. The goals and patterns of the constitutional movement, the philosophical and ideological foundations and criteria of the “National Constitution,” and the possibility and outcomes of parliamentary governance in Western Armenia have been revealed.
Keywords: Politics